MODERN LABORATORY DIAGNOSTICS OF NODULAR GOITER - Berdiyarova Shokhida Shukurullayevna; Najmiddinova Nigora Kamoliddinovna; Maksuddinova Munisa Shamsiddin kizi (TADQIQOTLAR.UZ, 2024)
Abstract: Nodular goiter is not just a physiological phenomenon, but a whole metaphor that permeates the life and being of many people. Its range of meanings ranges from purely medical aspects to deep philosophical reflections on existence. It seems to function in two planes: on the one hand, it is a manifestation associated with metabolic processes in the body, and on the other, it is a symbol of inner struggle and the search for harmony. In ancient texts, nodular goiter was often described through the prism of fear and misunderstanding. People who faced this disease felt the burden of prejudice and superstition. Over time, scientific progress has made it possible to look at nodular goiter as a challenge that must be met with courage and knowledge.